Correlations between chemical macro composition and redox potential for mineral waters from Truskavets deposit = Корреляции между химическим макросоставом и редокспотенциалом для минеральных вод Трускавецкого месторождения - V. Ya. Berezovskyy; O. R. Datsko; W. Zukow (Kazimierz Wielki University, 2015)
Berezovskyy V. Ya., Datsko O. R., Zukow W. Correlations between chemical macro composition and redox potential for mineral waters from Truskavets deposit = Корреляции между химическим макросоставом и редокспотенциалом для минеральных вод Трускавецкого месторождения. Journal of Education, Health and Sport. 2015;5(1):139-150. ISSN 2391-8306. DOI: 10.5281/zenodo.14551 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A139-150 https://pbn.nauka.gov.pl/works/530956 http://dx.doi.org/10.5281/zenodo.14551 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015.     CORRELATIONS BETWEEN CHEMICAL MACRO COMPOSITION AND REDOX POTENTIAL FOR MINERAL WATERS FROM TRUSKAVETS DEPOSIT   Корреляции между химическим макросоставом и редокспотенциалом для минеральных вод Трускавецкого месторождения   V. Ya. Berezovskyy1, O. R. Datsko1, W. Zukow2 В. Я. Березовский1, О. Р. Дацько1, В. Жуков2   1O.O. Bogomolets Institute Physiology National Academy of Sciences of Ukraine, Kyiv, Ukraine 1Институт физиологии им.А.А. Богомольца НАН Украины, Киев, Украина 2Kazimierz Wielki University, Bydgoszcz, Poland 2Uniwersytet Kazimierza Wielkiego, Bydgoszcz, Polska   Keywords: oxidation-reduction potential (ORP), potentiometry, chemical macro composition, mineral waters.   Ключевые слова: окислительно-восстановительный потенциал (ОВП), потенциометрия, химический макросостав, минеральные воды.   Abstract Correlations were researched between chemical macro composition and oxidation-reduction potential (ORP) measured by potentiometry for mineral waters from Truskavets deposit. It has been shown that mainly ORP values are correlated satisfactorily with hydrogen sulfide content and dissolved oxygen.   Резюме             Исследованы корреляции между химическим макросоставом и окислительно-восстановительным потенциалом (ОВП), измеренным потенциометрически для минеральных вод Трускавецкого месторождения. Показано, что в основном величины ОВП удовлетворительно коррелируют с концентрацией сероводорода и растворенного кислорода.